PROGRAM EDUKASI MANAJEMEN PENGOLAHAN IKAN BEREGULASI HALAL - Qori'ah, Maria; Fatimah, Nurul; Andriyanto, Dicky; Kumalaningrum, Dwi Retna; Subhan, Danil Hamdani (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Fish products are a nutritious food alternative for families and have high market value. The nutrients in fish are important for the body, especially for children. However, these beneficial nutrients are inseparable from quality assessment and fish processing management. This community service activity aims to educate the public and MSME actors in recognising and processing fish properly. The material presented not only focused on fish processing, but also on increasing the selling value, which was the focus of the community service activity. The selling value of fish products increases when they receive a certificate as a product label reinforcement. Therefore, material on the halal product certification process is important to complement the fish processing management material so that consumers are confident that the product quality is guaranteed. The enthusiastic participants consisted of PKK cadres and SMEs under the guidance of the village government. The results of the activity showed an increase in participants' understanding, as measured by discussions and hands-on practice accompanied by resource persons. The findings of this program are that fish nuggets are a superior product that is healthy and nutritious and has halal regulations with a mixture of bread as a substitute for flour.